Biosimilars for psoriasis: worldwide overview of regulatory guidelines, uptake and implications for dermatology clinical practice. (27th November 2017) - Cohen, A.D.; Wu, J.J.; Puig, L.; Chimenti, S.; Vender, R.; Rajagopalan, M.; Romiti, R.; de la Cruz, C.; Skov, L.; Zachariae, C.; Young, H.S.; Foley, P.; et al.
Summary: The introduction of biological drugs for the treatment of patients with psoriasis has revolutionized treatment paradigms and enabled numerous patients to achieve disease control with an acceptable safety profile. However, the high cost of biologics limits access to these medications for the majority of patients worldwide. In recent years, the introduction of biosimilars for inflammatory diseases has become a fast evolving field. The future use of biosimilars offers the potential for decreased cost and increased access to biologics for patients with psoriasis. For approval of biosimilars, different regulatory agencies use highly variable methods for definition, production, approval, marketing and postmarketing surveillance. Due to potential interchangeability between biologics and biosimilars, traceability and pharmacovigilance are required to collect accurate data about adverse events in patients with psoriasis; spontaneous reporting, registries and use of 'big data' should facilitate this process on a global basis. The current article describes biosimilar regulatory guidelines and examples of biosimilar uptake in clinical practice in several countries around the world. As it is apparent that biological therapy treatment decisions may become more physician independent, the International Psoriasis Council recommends that dermatologists should take an active role in the development of biosimilar prescribing policies with their respective healthcare settings and government agencies. Abstract : What's already known about this topic? The introduction of biosimilars for inflammatory diseases has become a fast evolving field. Development of biosimilars is anticipated to increase access to biological drugs and relieve part of the economic burden on health systems worldwide by providing lower‐cost medications. What does this study add? The current article describes the uptake of biosimilars for patients with psoriasis in various countries. There are substantial differences in biosimilar regulatory strategies and market access for biosimilars around the world. The International Psoriasis Council advocates that dermatologists take an active role in the development of biosimilar prescribing policies worldwide. Linked Comment:Kirby. Br J Dermatol 2017;177 :1473 .